Industrial training report: Perpustakaan Sultanah Nur Zahirah, Universiti Malaysia Terangganu / Nurul Dayana Muhammad Ali - Muhammad Ali, Nurul Dayana (Faculty of Information Management, 2018)
The purpose of this documentation is to report the activities undergone by the trainee during the Industrial Training for five months in Perpustakaan Sultanah Nur Zahirah (PSNZ). The report include daily task assigned to trainee such as learnt about acquisition, circulation, cataloguing, conducts the activities, digitization, data key in and others. In addition, the most important part is where the trainee has been assigned with a special project which are handling a part of big event in open day of library and also creating a barcode scanner for all citizens of Universiti Malaysia Terengganu (UMT). All of trainee should be responsible to give the best commitment in all these special project. So that, this special project will running smoothly suitable as planned in the schedule.